IMPROVEMENT OF ORGANIZATIONAL AND MANAGEMENT MECHANISMS OF IMPLEMENTATION OF THE STRATEGY IN THE ENTERPRISES OF THE TEXTILE INDUSTRY - Abdurahmonovich, Isaev Ravshan (The journal of contemporary issues in business and government, 2021)
The article examines the issues of improving the organizational and management mechanisms for the implementation of development strategies of textile enterprises in the integrated system of quality management and strategic management.